FYR Macedonia Energy Policy Paper - World Bank (Washington, DC, 2013)
This Report provides an overview of the investment, and policy choices in the Macedonian energy sector. On the investment side, the Report highlights the criteria under which potential investments in a new Combined Heat and Power (CHP) plant, and a new coal mine, should proceed. The Report focuses on reforms that would be required to support the CHP project, namely ratification by Macedonia of the Kyoto Protocol, and resolution of ownership issues related to the gas pipeline linking Skopje to Bulgaria. The Report recommends development of a Skopje gasification project, and a Renewable Energy Project. Regarding reforms to support Macedonia's participation in the regional energy market, the Report concludes that good progress is being made, particularly as regards development of a regulatory framework for the energy industry. The Report recommends that the Electric Power Company of Macedonia (ESM) be restructured, prior to privatization, with hydro assets being separated from thermal generation, and that possible ownership, be separated from thermal generation and distribution. The Report also questions the economic viability of the Skopje oil refinery, and recommends a review be undertaken. By and large, the report highlights the outstanding energy sector challenges, that fall in two broad categories: maintaining energy balance, and reform challenges. Regarding energy balance, the Government should support the most economically beneficial investment projects from the various alternatives. This (economics based decision making) neither a priori prefers, nor precludes, the use of domestic primary resources for energy supply. It is specified that further work is required to evaluate the economic benefits of new gas pipelines, which would facilitate transport of Caspian gas through Macedonia to western Europe.